POTRAYAL OF THE NINETEENTH CENTURY ENGLISH WOMEN IN JANE AUSTEN’S NOVEL SENSE AND SENSIBILITY - Alamsyah Alamsyah; Azmir Pasaribu; Zulfan Sahri (Universitas Islam Sumatera Utara (UISU), 2017)
The study has three points of discussion. The first deals with the rights of woman in obtaining property especially the one inherited from parents. The second does with the roles of women in the family. Once women married, their property rights are governed by English common law, legally absorbed by their husbands. Furthermore, married women could not make wills or dispose of any property without their husbands' consent. The third deals with the roles of women in society. A woman is surely forbidden to do any type of job or business. All is done by man. The main theory concerning property rights of women is proposed by Shanley (2000) who states that from the legal 'unity' of the husband and wife, it follows that a married woman could not sue or be sued unless her husband is also a party to the suit, could not sign contracts unless her husband joins her. And for the research method, the Descriptive Qualitative Approach proposed by Bogdan and Biklen (1992) is applied, concerning the opinions, experiences and feeling of individuals producing subjective data. It elaborates social phenomena as they occur naturally. The finding shows that all the female characters in the novel get into the problems of property rights, standings in family as well as in the society.